Differentiate y=e^(x)*sin(x) with respect to x

y=e^(x)*sin(x)   

Use the product rule:   y'=uv'+vu'    y=u*v          

Differentiate: u=e^(x)   u'=e^(x)    v=sin(x)  v'=cos(x)

Sub into the product rule: y'=e^(x)*cos(x)+e^(x)*sin(x)

Take out a factor of e^(x): y'=e^(x)*(cos(x)+sin(x))

Answered by Alexander J. Maths tutor

4402 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Why is there more than one solution to x^2 = 4?


y = 2ln(2x + 5) – 3x/2 , x > –2.5 find an equation to the normal of the curve when x = -2


How to factorise 6x^2-11x-10?


How would I find a the tangent of a point on a line?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences